ANALISIS KOMPARASI PEMBIAYAAN PROGRAM JAMINAN KESEHATAN NASIONAL DAN PROGRAM JAMINAN KESEHATAN DAERAH DALAM PENCAPAIAN EFEKTIFITAS ANGGARAN PADA DINAS KESEHATAN KABUPATEN BUOL - Timumun, Fatmawarda Sy. (Katalogis, 2018)
Comparative Financing Analysis of National Health Insurance Program and Regional Health Insurance in Achieving Budget Effektiveness in TheOffice of Health, Buol District. The study aims to compare the financing between national health insurance and Regional insurance program in Buol Districk by using a qualitative design. Informants of this study consist of 23 people hwo take part in the organization of national health insurance and Regional health insurance program in The office of health and community health centers in Buol District. The results of the study confirm that national health insurance funding concentrates on health and operational services at community health centers (Puskesmas); Regional health insurance funding allocates to providing health services at the local community health centers in Buol area and Hospitals in sentral Sulawesi in collaboration whit The Health offices ; it also funds activities in the Health office in Buol District. Budget allocationÂ for the national health insurance is relatively higher compared to Regional Health Insurance Program. Funding of the National Health Insurance is more sufficient that the allocation for the regional program. The national health Insurance program reaches SILPA every year, while the regional Health Insurance programÂ is always deficit. Management of the national health care programs in terms of budget utilization has not been effective in terms of service and budgetÂ utilization but ineffective in terms of budget provision.